Isolated internationalists : looking at North Korea through visual propaganda - Tan, Landson Lang Seng (2018)
North Korea's isolated development has allowed for it to develop a distinct visual style independent of major art trends within the Western world today, offering novel works that has attracted the attention of art collectors for its peculiar depictions of life within the closed state. Through them, propaganda posters that were previously inaccessible to the outside world were purchased and exhibited, allowing for outsiders to get a glimpse of life within the closed-off nation that adheres closely to its official Juche ideology. Besides its artistic value, propaganda posters offer interesting insights into North Korea's historical development that has stymied many observers due to a general lack of reliable information coming from within the state. The way different archetypes are portrayed within these posters can be traced back to appropriated symbols from the Soviet Union, revealing often surprising links between the North and other nations that are not traditionally within its sphere of interaction. As such, this paper seeks to provide a nuanced understanding into North Korea's historical developments through the iconographical analysis of its propaganda posters, challenging widely-held perceptions of its consistent isolation that many hold today.